1987
DOI: 10.1128/aac.31.2.274
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and mechanism of action of 3'-azido-3'-deoxythymidine (BW A509U)

Abstract: The thymidine analog 3'-azido-3'-deoxythymidine (BW A509U; azidothymidine [AZT]) had potent bactericidal activity against many members of the family Enterobacteriaceae, including strains of Escherichia coli, Salmonella typhimurium, Klebsiella pneumoniae, Shigella flexneri, and Enterobacter aerogenes. AZT also had bactericidal activity against Vibrio cholerae and the fish pathogen Vibrio anguillarum. AZT had no activity against Pseudomonas aeruginosa, gram-positive bacteria, anaerobic bacteria, Mycobacterium tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
122
0

Year Published

1988
1988
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(132 citation statements)
references
References 25 publications
10
122
0
Order By: Relevance
“…We assayed colony formation in the presence of low levels of the replication inhibitor AZT, which causes DNA chain termination during DNA synthesis (6) and is only expected to damage replicating cells. Null mutants in iraD exhibited dramatic hypersensitivity to AZT (Fig.…”
Section: Isolation and Characterization Of An Irad Transposon Insertimentioning
confidence: 99%
See 1 more Smart Citation
“…We assayed colony formation in the presence of low levels of the replication inhibitor AZT, which causes DNA chain termination during DNA synthesis (6) and is only expected to damage replicating cells. Null mutants in iraD exhibited dramatic hypersensitivity to AZT (Fig.…”
Section: Isolation and Characterization Of An Irad Transposon Insertimentioning
confidence: 99%
“…Phleomycin induces random single-or double-strand breaks in the backbone of DNA (5), whereas AZT blocks DNA synthesis, leading to single-strand gaps in the replication fork (6). One insertion mutant in iraD (previously an unknown gene, yjiD) was hypersensitive to phleomycin and AZT.…”
mentioning
confidence: 99%
“…44 Incorporation of AZT into DNA results in chain termination and ultimately cell death. 44 Therefore, AZT also acts as an antibacterial agent, and previous studies have reported activity against Escherichia, Enterobacter, Klebsiella, Salmonella, and Shigella. [44][45][46][47] Our findings are therefore consistent with prior studies performed with a small number of carbapenem-susceptible Enterobacteriaceae strains.…”
mentioning
confidence: 99%
“…42,43 However, AZT is also a substrate for bacterial thymidine kinase (TK). 44 TK, a critical part of the thymidine salvage pathway, catalyzes the first of three phosphorylation events that make thymidine or AZT competent for incorporation into DNA. 44 Incorporation of AZT into DNA results in chain termination and ultimately cell death.…”
mentioning
confidence: 99%
See 1 more Smart Citation